THE ROLE OF BIOMARKERS IN EARLY DISEASE DIAGNOSIS IN CLINICAL LABORATORY MEDICINE - Uzoqova Bibisora; Nurmatova M.A. (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. Biomarkers play a crucial role in modern clinical laboratory medicine, particularly in the early detection and monitoring of diseases. A biomarker is a measurable biological indicator that reflects normal biological processes, pathogenic processes, or responses to therapeutic interventions. With the advancement of laboratory technologies, biomarkers have become essential tools in diagnosing cardiovascular diseases, cancer, infections, and metabolic disorders at early stages.Early diagnosis significantly improves treatment outcomes and reduces morbidity and mortality rates. Laboratory-based biomarker testing provides rapid, accurate, and minimally invasive diagnostic information that supports clinical decision-making. This article discusses the classification of biomarkers, their clinical applications, and their importance in early disease detection and personalized medicine [1].